Metal Supply Chain Coordination with Revenue-sharing Contract: A Case Study in Khuzestan Steel Company - Dolat-Abadi, Hossein Mohammadi; Karimi, Sajjad (International Journal of Industrial Engineering: Theory, Applications and Practice, 2025)
This paper aims to model a Metal Supply Chain to optimize the price and order quantity under decentralized and coordinated decision-making strategies in a two-level supplier-manufacturer chain. Modeling of this supply chain was performed concerning the leadership of one member and the following of another member using the Stackelberg game model. In this study, a revenue-sharing contract is used to create a coordination strategy in the steel supply chain, and sensitivity analysis on key variables is performed. The results of this research can help improve the profitability of the members in the MSC under a coordinated approach using a revenue-sharing contract compared to a decentralized one. The results of the sensitivity analysis demonstrated that with the increase in product quality, the total profit of the supply chain increases in both coordinated and decentralized modes, while the coordinated strategy yields a greater increase in total profit than the decentralized one.